2015
DOI: 10.1016/j.celrep.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Stem Cell Self-Renewal Is Regulated by Slit2/Robo1 Signaling through SNAI1 and mINSC

Abstract: Summary Tissue homeostasis requires somatic stem cell maintenance; however, mechanisms regulating this process during organogenesis are not well understood. Here, we identify asymmetrically renewing basal and luminal stem cells in the mammary end bud. We demonstrate that SLIT2/ROBO1 signaling regulates the choice between self-renewing asymmetric cell divisions (ACDs) and expansive symmetric cell divisions (SCDs) by governing Inscuteable (mInsc), a key member of the spindle orientation machinery, through the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 43 publications
(59 reference statements)
0
68
0
Order By: Relevance
“…However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014. Similar roles for LGN in promoting perpendicular/ asymmetric divisions have been reported in retina and mammary gland (Ballard et al, 2015;Chiu et al, 2016;Lacomme et al, 2016). The molecular mechanisms that regulate the differential subcellular localization of LGN in progenitors undergoing both symmetric and asymmetric cell divisions remain largely unknown.…”
Section: Discussionmentioning
confidence: 67%
“…However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014. Similar roles for LGN in promoting perpendicular/ asymmetric divisions have been reported in retina and mammary gland (Ballard et al, 2015;Chiu et al, 2016;Lacomme et al, 2016). The molecular mechanisms that regulate the differential subcellular localization of LGN in progenitors undergoing both symmetric and asymmetric cell divisions remain largely unknown.…”
Section: Discussionmentioning
confidence: 67%
“…Slit-Robo signaling also controls the division mode of mammary stem cells: in the absence of Robo1, symmetric divisions are favored rather than asymmetric ones (Ballard et al, 2015). This is due to an increase in the spindle apparatus protein Insc.…”
Section: Slit-robo Signaling In Organogenesismentioning
confidence: 99%
“…Our data showing that the region between Ϫ5,382 and Ϫ4,712 bases upstream has higher promoter activity than the minimum promoter implicates a co-regulatory element that drives mouse Insc expression within the region between Ϫ5,382 and Ϫ5,066, although this region alone is not sufficient for promoter activity. While we were preparing this manuscript, Ballard et al (58) reported that SNAL1 enhances mouse Insc expression in mammary stem cells. They used a 224-bp DNA fragment containing the upstream region of human Inscuteable for luciferase assays.…”
Section: Discussionmentioning
confidence: 99%